Reason and the Critique of Reason in Heidegger’s Thought - Pretzsch, Moritz René (Problemos, 2025)
If, in the history of philosophy, all manifestations of culture were brought before the judgment seat of reason, today it seems rather the other way around, as if reason were on trial. Has reason, the question arises, reached the end of its history and even the end itself? Hardly any thinker before him has undermined, depreciated and dissolved reason as much as Martin Heidegger. The actual main point of Heidegger’s critique of reason is the questioning of the centuries-old understanding of human beings as animal rationale. According to Heidegger, an understanding ofhuman beings as animal rationale prevents the ‘clearing’ [Lichtung] of being. For this reason, Heidegger continues, we must be careful not to resort to any ‘properties’ and ‘capabilities’ of human beings, for example, to reason. This article aims to determine the validity of this warning today and to what extent Heidegger’s thinking of reason and critique of reason can claim current philosophical relevance. First, Heidegger’s engagement with Kant and Husserl will be examined, along with his attempt to reflect on the origin of reason and logic. Subsequently, the focus will be on Heidegger’s critical engagement with the calculating thinking of modernity and the influential figures of thought ‘machination’ [Machenschaft] and ‘enframing’ [Ge-Stell], in order to conclude with a short reference to the present. In doing so, I will comment, in particular, on two central aspects of Heidegger’s thinking on reason and offer a brief outlook.